APPRAISAL OF THE STUDIES ON MATURATION AND SPAWNING IN MARINE TELEOSTS FROM THE INDIAN WATERS - Qasim, S Z (Indian Journal of Fisheries, 2011)
Maturation and spawing in many teleosts from the Indian waters have been studied by different authors using conventional methods. The most common among these methods are seasonal changes in the condition of gonads and the ova diameter frequency distribution. The latter is supposed to give an index of the progression of oocytes and their withdrawal from the ovaries. There are several drawbacks in these methods, as they were essentially developed for fishes from the temperate regions. It is therefore desirable that other methods should also be used for arriving at a realistic picture of the spawning process. Maturity is clearly linked with the growth rate of fishes and hence the two phases—pre-and post-maturity—should be clearly distinguished. Spawning in a population is possibly geared to external events, when conditions for the newly produced broods are most favourable. Fishes in the Indian waters spawn in all the months of the year, but along the east coast spawning largely seems to occur during the pre-monsoon months and along the west coast during the monsoon and post-monsoon months. Many species appear to be continuous breeders, and hence to develop a clear understanding of their maturation and spawning, it is necessary to make observations throughout the year.